2021
DOI: 10.1128/jvi.02358-20
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Biogenesis of Novel Vesicles Containing Viral Products in Human Cytomegalovirus Infection

Abstract: Human cytomegalovirus (HCMV), while highly restricted for the human species, infects an diverse array of cell types in the host. Patterns of infection are dictated by the cell type infected, but cell type-specific factors and how they impact tropism for specific cell types is poorly understood. Previous studies in primary endothelial cells showed that HCMV infection induces large multivesicular-like bodies (MVBs) that incorporate viral products, including dense bodies (DBs) and virions. Here we define the natu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 96 publications
(96 reference statements)
1
26
0
Order By: Relevance
“…It is plausible to hypothesize that these virus populations might undergo different envelopment processes in the cell and are exocytosed with a different spatiotemporal profile (Scrivano et al, 2011). While this manuscript was in preparation, a study from the Wilson and Goodrum lab suggested that virus-containing MVBs in fibroblasts and endothelial cells are derived from different cellular membranes, which would add another potential HCMV egress pathway that could result in different virus populations; however, it is unclear if these pathways are functional in egress (Momtaz et al, 2021). Future work needs to focus on characterizing the particle populations that are exocytosed by these pathways with regards to their glycoprotein content and define their role in potentially divergent egress routes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is plausible to hypothesize that these virus populations might undergo different envelopment processes in the cell and are exocytosed with a different spatiotemporal profile (Scrivano et al, 2011). While this manuscript was in preparation, a study from the Wilson and Goodrum lab suggested that virus-containing MVBs in fibroblasts and endothelial cells are derived from different cellular membranes, which would add another potential HCMV egress pathway that could result in different virus populations; however, it is unclear if these pathways are functional in egress (Momtaz et al, 2021). Future work needs to focus on characterizing the particle populations that are exocytosed by these pathways with regards to their glycoprotein content and define their role in potentially divergent egress routes.…”
Section: Discussionmentioning
confidence: 99%
“…While the previous literature often called these virus-containing multivesicular structures "MVBs", we decided to dub them multi-viral bodies (MViB) as we could not untangle their descent clearly. A recent study from the Wilson and Goodrum labs suggested that virus-containing structures in HCMV fibroblasts and endothelial cells are derived from membranes of different cellular origins [26]. Importantly, a functional role for these "virus-containing MVBs" or "MViBs" in egress has lacked so far [14,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although current data (Read et al, 2019;Schauflinger et al, 2013;Shaga Devan et al, 2021;Taisne et al, 2019) have mainly described that HCMV capsids individually bud into small vesicles in the AC (Figure 1a,b), several studies have described large vesicles filled with virus particles (Bughio et al, 2013;Fraile-Ramos et al, 2010;Momtaz et al, 2021;Schauflinger et al, 2011;Severi et al, 1988).…”
Section: H CMV Us E S Mv Ibs For Intermit Tent Bulk Rele a S E Of Vir...mentioning
confidence: 95%